Buying Intentions and Antecedents Affecting Online Shopping of the Silver Generation Consumers in Bangkok - Wongbangpo, Praphan (Ph.D. in Social Sciences Journal, 2023)
This research article aims to study the impact of digital literacy, digital anxiety, self-efficacy, perceived ease of use, perceived usefulness, and the intention to shop online on the online shopping of the silver generation consumers in Bangkok. As a quantitative research, online questionnaires were employed to gather data from 500 silver age consumers who had experience on the online shopping. Then the data were analyzed by the descriptive analysis and then the hypotheses defined by the Structural Equation Model were tested and analyzed by the AMOS software program. Findings are as follows: The silver generation consumers observed high level of the digital literacy, self-efficacy, perceived ease of use, perceived usefulness, and the intention to shop online, while their anxiety about the digital were at the medium level. These silver generation consumers were also at moderate level regarding the online shopping. Also, the intention to shop online had direct impact on the actual online shopping. Moreover, the digital literacy, digital anxiety, self-efficacy, perceived ease of use, and perceived usefulness had indirect effect on the actual online shopping behavior through the intention to shop online. The result of this study implied that silver generation consumers had begun to accept technology, as well as online shopping. This would result in online shopping behavior eventually.